A one-pot synthesis of 3-trifluoromethyl-2-isoxazolines from trifluoromethyl aldoxime - Gonçalves, Raoni S. B.; Dos Santos, Michael; Bernadat, Guillaume; Bonnet-Delpon, Danièle; Crousse, Benoit (Beilstein Journal of Organic Chemistry, 2013)
Functionalized 3-trifluoromethyl-2-isoxazolines and 3-trifluoromethylisoxazoles were easily prepared from trifluoromethyl aldoxime 2 under mild conditions by using DIB as oxidant. Theoretical studies of the reactivity of trifluoroacetonitrile oxide 4 toward olefins and alkynes were carried out. The 3-trifluoromethyl-2-isoxazolines were ring-opened with NaBH4 and NiCl2 to yield the corresponding trifluoromethylated γ-amino alcohols.
Keywords: aldoxime; amino alcohol; fluorine; isoxazole; isoxazoline; organo-fluorine

Nitrile oxides, nitrones, and nitronates in organic synthesis - Feuer, H. (John Wiley & Sons, 2008)

Progress in Heterocyclic Chemistry - Cicchi, S.; Cordero, F. M.; Giomi, D. (Five-membered ring systems: With O&N atoms, 2003)

Synthesis of Heterocycles via Cycloadditions I - Namboothiri, I. N. N.; Rastogi, N. (Isoxazolines from Nitro Compounds: Synthesis and Applications, 2008)

(untitled) - Savage, G. P. (Curr. Org. Chem., 2010)

(untitled) - El Sayed, K. A.; Bartyzel, P.; Shen, X.; Perry, T. L.; Zjawiony, J. K.; Hamann, M. T. (Tetrahedron, 2000)

(untitled) - Proksch, P.; Putz, A.; Ortlepp, S.; Kjer, J.; Bayer, M. (Phytochem. Rev., 2010)

(untitled) - Castellano, S.; Kuck, D.; Viviano, M.; Yoo, J.; López-Vallejo, F.; Conti, P.; Tamborini, L.; Pinto, A.; Medina-Franco, J. L.; Sbardella, G. (J. Med. Chem., 2011)

(untitled) - Dallanoce, C.; Frigerio, F.; Martelli, G.; Grazioso, G.; Matera, C.; Pomè, D. Y.; Pucci, L.; Clementi, F.; Gotti, C.; De Amici, M. (Bioorg. Med. Chem., 2010)

(untitled) - Cheng, J.-F.; Huang, Y.; Penuliar, R.; Nishimoto, M.; Liu, L.; Arrhenius, T.; Yang, G.; O'Leary, E.; Barbosa, M.; Barr, R.; Dyck, J. R. B.; Lopaschuk, G. D.; et al. (J. Med. Chem., 2006)

(untitled) - Benltifa, M.; Hayes, J. M.; Vidal, S.; Gueyrard, D.; Goekjian, P. G.; Praly, J.-P.; Kizilis, G.; Tiraidis, C.; Alexacou, K.-M.; Chrysina, E. D.; Zographos, S. E.; Leonidas, D. D.; et al. (Bioorg. Med. Chem., 2009)

(untitled) - Rakesh; Sun, D.; Lee, R. B.; Tangallapally, R. P.; Lee, R. E. (Eur. J. Med. Chem., 2009)

(untitled) - Tangallapally, R. P.; Sun, D.; Rakesh; Budha, N.; Lee, R. E. B.; Lenaerts, A. J.; Meibohm, B.; Lee, R. E. (Bioorg. Med. Chem. Lett., 2007)

(untitled) - Tang, S.; He, J.; Sun, Y.; He, L.; She, X. (J. Org. Chem., 2010)

(untitled) - Jiang, D.; Chen, Y. (J. Org. Chem., 2008)

(untitled) - Maimone, T. J.; Shi, J.; Ashida, S.; Baran, P. S. (J. Am. Chem. Soc., 2009)

Fluorine in Organic Chemistry - Chambers, R. D. (Blackwell Publishing Ltd., 2004)

(untitled) - O'Hagan, D. (Chem. Soc. Rev., 2008)

Bioorganic and Medicinal Chemistry of Fluorine - Bégué, J.-P.; Bonnet-Delpon, D. (Wiley, 2008)

Organofluorine Chemistry - Uneyama, K. (Blackwell Publishing, 2006)

Modern Fluoroorganic Chemistry - Kirsch, P. (Wiley, 2004)

Organofluorine Chemistry, Principles and Commercial Applications - Banks, R. E.; Smart, B. E.; Tatlow, J. C. (Plenum, 1994)

(untitled) - Woods, J. R.; Mo, H.; Bieberich, A. A.; Alavanja, T.; Colby, D. A. (J. Med. Chem., 2011)

(untitled) - Jordan, J. B.; Poppe, L.; Xia, X.; Cheng, A. C.; Sun, Y.; Michelsen, K.; Eastwood, H.; Schnier, P. D.; Nixey, T.; Zhong, W. (J. Med. Chem., 2012)

(untitled) - Dalvit, C. (Prog. Nucl. Magn. Reson. Spectrosc., 2007)

(untitled) - Tanaka, K.; Masuda, H.; Mitsuhashi, K. (Bull. Chem. Soc. Jpn., 1984)

(untitled) - Yoshimura, A.; Zhu, C.; Middleton, K. R.; Todora, A. D.; Kastern, B. J.; Maskaev, A. V.; Zhdankin, V. V. (Chem. Commun., 2013)

(untitled) - Mendelsohn, B. A.; Lee, S.; Kim, S.; Teyssier, F.; Aulakh, V. S.; Ciufolini, M. A. (Org. Lett., 2009)

(untitled) - Shing, T. K. M.; Wong, W. F.; Cheng, H. M.; Kwok, W. S.; So, K. H. (Org. Lett., 2007)

(untitled) - Singh, V.; Hutait, S.; Biswas, S.; Batra, S. (Eur. J. Org. Chem., 2010)

(untitled) - Pinto, A.; Conti, P.; Grazioso, G.; Tamborini, L.; Madsen, U.; Nielsen, B.; De Micheli, C. (Eur. J. Med. Chem., 2011)

(untitled) - Minakata, S.; Okumura, S.; Nagamachi, T.; Takeda, Y. (Org. Lett., 2011)

(untitled) - Zhdankin, V. V.; Stang, P. J. (Chem. Rev., 2008)

(untitled) - Bégué, J.-P.; Bonnet-Delpon, D.; Crousse, B. (Synlett, 2004)

(untitled) - Shuklov, I. A.; Dubrovina, N. V.; Börner, A. (Synthesis, 2007)

(untitled) - Middleton, W. J. (J. Org. Chem., 1984)

(untitled) - Houk, K. N.; Sims, J.; Duke, R. E.; Strozier, R. W.; George, J. K. (J. Am. Chem. Soc., 1973)

(untitled) - Houk, K. N.; Sims, J.; Watts, C. R.; Luskus, L. J. (J. Am. Chem. Soc., 1973)

(untitled) - Lan, Y.; Zou, L.; Cao, Y.; Houk, K. N. (J. Phys. Chem. A, 2011)

(untitled) - Kohn, W.; Sham, L. J. (Phys. Rev., 1965)

(untitled) - Hohenberg, P.; Kohn, W. (Phys. Rev., 1964)

(untitled) - Becke, A. D. (J. Chem. Phys., 1993)

(untitled) - Lee, C.; Yang, W.; Parr, R. G. (Phys. Rev. B, 1988)

Ab Initio Molecular Orbital Theory - Hehre, W. J.; Radom, L.; Schleyer, P. V. R.; Pople, J. (Wiley, 1986)

(untitled) - Havasi, B.; Pasinszki, T.; Westwood, N. P. C. (J. Phys. Chem. A, 2005)

(untitled) - Sustmann, R. (Pure Appl. Chem., 1974)

(untitled) - Michaut, V.; Metz, F.; Paris, J.-M.; Plaquevent, J.-C. (J. Fluorine Chem., 2007)

(untitled) - Sukach, V. A.; Golovach, N. M.; Pirozhenko, V. V.; Rusanov, E. B.; Vovk, M. V. (Tetrahedron: Asymmetry, 2008)

(untitled) - Huguenot, F.; Brigaud, T. (J. Org. Chem., 2006)

(untitled) - Tanaka, K.; Sugimoto, Y.; Okafuji, Y.; Tachikawa, M.; Mitsuhashi, K. (J. Heterocycl. Chem., 1989)

(untitled) - Nonn, M.; Kiss, L.; Sillanpää, R.; Fülöp, F. (Beilstein J. Org. Chem., 2012)